Fortifikasi Pakan Ikan dengan Tepung Cacing Sutra (Tubifex sp) pada Fase Pembesaran Lele Sangkuriang (Clarias gariepinus) - Hamron, Novita; Warman, Indra; Sari, Hety Novita; Oktamalia; Sari, Dia Novita; Togatorop, Eny Rolenti (PendIPA Journal of Science Education, 2024)
The development of feed technology with the fortification of silkworm flour (Tubifex sp) is one solution that can be attempted. The silkworm contains high protein. This study aimed to analyze the effect of fish feed fortification with silkworm flour on the growth phase of Sangkuriang catfish. This research method used a Completely Randomized Design on one factor with three replications. The factors used were four treatments including A (95% fish flour + 5% silkworm flour), B (90% fish flour + 10% silkworm flour), C (85% fish flour + 15% silkworm flour), and D (80% fish flour + 20% silkworm flour). The results showed that the rate of length increase and weight increase of Sangkuriang catfish significantly increased when the catfish were in the 20-day enlargement phase in the tarpaulin pond. Treatment C (85% fish meal + 15% silkworm meal) was the best feed formulation seen in the high absolute weight growth (23,67 g), daily growth rate (2,66%), and feed utilization efficiency (1,32%). The results of this study can used as a reference in making artificial feed for the enlargement of Sangkuriang catfish.